HUBUNGAN TINGKAT PENGETAHUAN DAN PRAKTIK PERSONAL HYGIENE DENGAN KEJADIAN PENYAKIT SCABIES DI LINGKUNGAN PONDOK PESANTREN RAUDLATUT TA’ALLUM WILAYAH KERJA PUSKESMAS SANGKALI TAHUN 2023 - Dwiyanti, Nila Sari; Neni, Neni; Muharry, andy (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2024)
Background: Scabies is still a global public health problem. One place that has the potential to become a place for transmission of scabies is Islamic boarding school. Sangkali Community Health Center is one of the community health centers in Tasikamalaya City which experiences an increase in scabies cases every year, most of which come from the Raudhatul Ta'alum Islamic boarding school. Objective: To determine the relationship between the level of knowledge about scabies and the personal hygiene behavior of students with the incidence of scabies in the Raudlatut Ta'Allum Islamic Boarding School environment in the Sangkali Community Health Center working area. Method: This research is a quantitative research with a case control design. The research sample consisted of 59 case groups and 59 control groups. Sampling used total sampling technique. Data analysis used the chi-square. test. Results: This research shows that students' personal hygiene knowledge and behavior is related to the incidence of scabies at the Raudhatul Ta'alum Islamic boarding school. Students are expected to start maintaining personal hygiene, such as avoiding sharing items, regularly bathing twice a day and regularly changing bedding.